Dakwah Fiqih Darah Perempuan di Media Sosial: Studi Terhadap Akun Instagram @dailyhaid - Ma'rufah, Hafidhoh (Alhadharah: Jurnal Ilmu Dakwah, 2023)
Technology has brought changes to the result of women's blood science propaganda on social media. In some traditions, menstruation is considered a taboo thing to discuss openly. Even women who experience menstruation have to undergo certain rituals that are patriarchal. This research is a qualitative case study research and uses descriptive data analysis. By using Pierre Felix Bourdieu's theoretical approach, this article attempts to explore @dailyhaid's da'wah strategy so that it is accepted by various circles of Indonesian Muslim society, how the @dailyhaid Instagram account attempts to educate the public about the science of women's blood through social media, and what is behind it. Hence, it dares to raise the previously considered taboo theme in public spaces. An important finding from this research is that there are rational and emotional reasons. Sound in the form of choosing Instagram as a medium to reach a wider community and passionate in the form of the founder's empathy for the lack of knowledge of Muslim women regarding the science of women's blood jurisprudence. Apart from that, there is some capital that @dailyhaid has so it can be accepted in society. Some of their money, part of traditionalist circles, can strengthen religious authority on social media. In this case, content determination also uses Islamic boarding school methods, such as using classical literature or the Yellow Book. Second, the ability to master technology. KEYWORDS: da'wah; woman's blood; social media; religious authority. Artikel berikut mengkaji mengenai perkembangan teknologi yang telah memberikan kebebasan masyarakat dalam mencari informasi dan mereduksi hal-hal tabu. Teknologi membawa perubahan bagi perkembangan dakwah ilmu darah wanita di media sosial. Dalam beberapa tradisi, menstruasi dianggap sebagai hal yang tabu untuk dibicarakan secara terbuka. Bahkan perempuan yang mengalami menstruasi harus menjalani ritual tertentu yang bersifat patriarkis. Dengan memakai pendekatan teori habitus milik Pierre Felix Bourdieu, artikel ini berupaya menggali strategi dakwah @dailyhaid sehingga diterima di berbagai kalangan masyarakat muslim Indonesia, bagaimana upaya akun instagram @dailyhaid mengedukasi masyarakat tentang ilmu darah wanita melalui media sosial, dan apa yang melatarbelakangi sehingga berani mengangkat tema yang dulunya dianggap tabu ke ruang publik. Selain menjadi angin segar bagi banyak kalangan, terutama perempuan, @dailyhaid juga merupakan bagian dari kalangan tradisionalis yang melakukan penguatan otoritas keagamaan di media sosial. Cara penentuan konten juga menggunakan cara-cara pesantren, seperti penggunakan literatur klasik atau kitab kuning. Tidak hanya fokus terhadap materi, akun dakwah ini juga fokus berdakwah dengan inovatif dan kreatif agar diterima di banyak kalangan, terutama kalangan luar pesantren.